DUE PROCESS OF LAW DALAM SISTEM PERADILAN PIDANA DI INDONESIA KAITANNYA DENGAN PERLINDUNGAN HAM - Rahmat Efendy Al Amin Siregar (IAIN Padangsidimpuan, 2015)
Abstract: Basic rights are fundamental necessities of human beings. They are God’s natural gifts that should be respected as human dignity. In law, the criminal judicature process is set up from investigation, prosecution to court session. Actually, the efforts to implement human basic right into the law are to ensure the highest value of justice and humanity in accordance with the dignity of free people. Even though in the due process of law, the police have been given special rights or privileges to implement the function of investigating by the law to summon, examine, seize, arrest, search, confiscate something from the accused, they have to obey the due process of law principle itself. The law enforcing people’s adherence to the right of due process of law makes the accused have the right to be investigated according to the law of procedure. To realize this concept of due process of law relating to human basic rights in handling the criminal act, nobody is or can place himself/herself above the law, but he/she has to uphold the law supremacy and the law should be applied to anybody based on the principle of similar and fair treatment.Keywords: Criminal Justice System, Human Rights Abstrak: Hak-hak dasar adalah kebutuhan dasar manusia. Mereka adalah karunia alami Allah yang harus dihormati sebagai martabat manusia. Dalam hukum, proses peradilan pidana diatur dari penyidikan, penuntutan ke persidangan. Sebenarnya, upaya untuk melaksanakan hak dasar manusia ke dalam hukum adalah untuk memastikan nilai tertinggi keadilan dan kemanusiaan sesuai dengan martabat orang bebas. Meskipun dalam proses hukum, polisi telah diberikan hak khusus atau hak istimewa untuk melaksanakan fungsi menyelidiki oleh hukum untuk memanggil, memeriksa, menangkap, menahan, pencarian, menyita sesuatu dari terdakwa, mereka harus mematuhi karena proses prinsip hukum itu sendiri. Penegak hukum patuh terhadap masyarakat dalam kebenaran proses hukum membuat, terdakwa memiliki hak untuk diselidiki sesuai dengan hukum acara. Untuk mewujudkan konsep ini proses hukum yang berkaitan dengan hak asasi manusia dalam menangani tindak pidana, tidak ada yang dapat menempatkan dirinya di atas hukum, tetapi ia / dia harus menegakkan supremasi hukum dan hukum harus diterapkan kepada siapa saja berdasarkan prinsip perlakuan yang sama dan adil.Kata Kunci: Sistem Peradilan Pidana, Hak Asasi Manusia